Does wastewater surveillance have a role in vaccine-preventable disease control? Comparison of clinical and wastewater surveillance data for hepatitis A, E, measles, rubella and influenza viruses NICD, South Africa, 2021-2024 - Dr Kerrigan McCarthy; Ms Chenoa Sankar; Mr Victor Mabasa; Ms Nosi Msomi; Mr Emmanuel Phalane; Ms Mokgaetji Macheke; Mr Sipho Gwala; Ms Natasha Singh; Ms Phindile Ntuli; Mr Nkosenhle Lindo Ndlovu; Ms Fiona Els; Ms Sibonginkosi Maposa; et al. (International Journal of Infectious Diseases)
Introduction: Wastewater and environmental surveillance (WES) has provided valuable quantitation and sequencing data for polio, SARS-CoV-2 and Mpox to support public health decision-making. We aimed to determine if WES for vaccine-preventable diseases (VPDs) is possible and if it may complement clinical surveillance for hepatitis A, E, measles, rubella and influenza viruses. Methods: Digital PCR (dPCR) assays using disease-specific primers were incorporated into single and multiplex reactions that were optimized using positive controls (viral culture, RNA plasmids or known clinical samples). Limits of quantification for each pathogen were determined using quantitative (qPCR) and dPCR on serial dilutions of positive controls. Retained concentrates from wastewater samples collected from 48 national wastewater treatment plants or district sampling networks in nine South African provinces for SARS-CoV-2 wastewater surveillance were subjected to batched RNA extraction and dPCR testing for VPDs. Results of wastewater testing and national notifiable medical conditions surveillance data were compared by epidemiological week and district of collection. Influenza wastewater results were compared with reference to the influenza season (during, before and after) as determined by clinical sentinel site surveillance data. Results: Limits of quantification in genome copies/mL were as follows hepatitis A: 260; hepatitis E: 400; measles: 590; rubella: 460; influenza A&B: 1000. Amongst retrospective wastewater samples the proportion testing positive were; hepatitis A: 425/2329 (18%); hepatitis E: 280/2329 (12%), measles: 47/2422 (1.9%); rubella 39/2422 (1.6%), influenza A: 113/2422 (4.7%); influenza B: 72/2422 (3%). When compared with clinical results, wastewater results were positive when clinical cases were found in the same district and epidemiological week amongst 26%, 8%, 3% and 1% of time-district pairs for hepatitis A, E, measles and rubella respectively. However, the virus was detected in wastewater when no clinical cases were reported that week amongst 4%, 25%, 3% and 4% of time-district pairs for hepatitis A, E, measles and rubella respectively. Regarding influenza A, the majority of wastewater samples tested positive during the season (44/80 positive samples, 55%) than before or after, whilst the majority of influenza B detections in 2023 were after the season (28/36 positive samples, 77%) Discussion: In our comparison of clinical and wastewater data for hepatitis A, E, measles and rubella, WES found evidence of circulating virus in wastewater on multiple occasions in districts when clinical surveillance failed to find cases. Clinical surveillance may be limited on account of test unavailability, absent health seeking, and cases being asymptomatic or minimally symptomatic. Public health action following wastewater detection in the absence of clinical cases should be determined by contextual factors (availability and coverage of vaccination, consequences of ongoing transmission, disease burden) and specific aims of disease control programmes. Conclusion: Wastewater detection of vaccine preventable diseases is possible and may complement VPD surveillance and control programmes